2016
DOI: 10.1080/10426914.2016.1198038
|View full text |Cite
|
Sign up to set email alerts
|

Energy coupled to matter for magnetic alignment of rare earth–doped alumina

Abstract: Energy Coupled to Matter concepts such as magnetic field-assisted processing were used to align rare earth-doped alumina ceramics in the presence of applied fields. The addition of gadolinium and ytterbium dopants to alumina increased the magnetic susceptibility anisotropies, and induced magnetic torques that led to significant alignment of ceramic particles under the application of magnetic fields as low as 1.8 Tesla. In comparsion, undoped alumina materials showed minimal alignment under applied field streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Past research suggests that the total magnetic moment in the super cell may only be a partial descriptor of magnetic activity and that it is possible for dopants which are not typically considered to be good candidates for inducing magnetism to induce non-localized spin densities that are superior for texturing purposes [8,19]. It is important, therefore, to characterize not just the total magnetic moment, but also how widely distributed the magnetic moment is.…”
Section: Magnetic Moment and Spin Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…Past research suggests that the total magnetic moment in the super cell may only be a partial descriptor of magnetic activity and that it is possible for dopants which are not typically considered to be good candidates for inducing magnetism to induce non-localized spin densities that are superior for texturing purposes [8,19]. It is important, therefore, to characterize not just the total magnetic moment, but also how widely distributed the magnetic moment is.…”
Section: Magnetic Moment and Spin Densitymentioning
confidence: 99%
“…However, the birefringent nature of the material has limited the application of polycrystalline alumina optical systems [5]. Research has shown that it is possible to texture alumina with the application of a strong external magnetic field, thereby reducing the degree of internal reflection and refraction of light and increasing its transparency [6][7][8]. Our initial research focused on Cr, Fe, Ni, and Cu doped alumina in an effort to strengthen the coupling between alumina and applied external magnetic fields [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible approach to decreasing the scattering of light in polycrystal line alumina is through texturing, which can have a profound affect on the physical and optical properties of a material [6,7]. Research of slip cast doped alumina has shown that it is possible to texture alumina with the application of a strong external magn etic field [8][9][10]. Doping alumina in a way that leads to net unpaired electrons could strengthen the coupling between it and external magnetic fields, improving the effi ciency of texturing with a magnetic field and allowing for the creation of advanced high strength, chemically resistant sys tems such as spintronic and magnetic qubit systems [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that substituting a transition metal dopant could produce alumina that possesses both unpaired electrons and a net magnetic moment 12 . In addition, it was also determined that the delocalization of these unpaired electrons varied greatly between dopants 13 , which may affect the final magnetic properties of the doped system 14 . Previous work in metallic systems 15 17 has pointed toward enhanced magnetism near surfaces, where a transition in spin density from the bulk to the surface region was observed.…”
mentioning
confidence: 99%